Sexual Violence Perpetration as a Risk Factor for Current Depression or Posttraumatic Symptoms in Adolescents - Meadows, Amy L. (Journal of interpersonal violence, 2022)
Sexual violence perpetration (SVP), including coerced, physically forced, and alcohol- or drug-facilitated unwanted sex, occurs frequently in adolescence and may represent a risk factor for future perpetration. Sexual violence victimization (SVV) has been found to be a risk factor for increased rates of depression and posttraumatic stress disorder (PTSD); however, the associations of SVP with depression or posttraumatic stress symptoms (PTSS) have been less well described. This study examined associations between symptoms of depression and PTSS with SVP in the prior 12 months among high school students. In this cross-sectional analysis, a representative sample of public high school students (ninth–12th grades) completed self-reported surveys on peer SVP and SVV within the past year. Among 16,784 students completing surveys, 7.2% disclosed SVP against another high school student in the past 12 months; 64.4% of students disclosing SVP also experienced SVV. Both SVP and SVV, alone or in combination, were associated with a greater likelihood of symptoms of depression or PTSS. These associations were similar by sex and sexual minority status (e.g., lesbian, gay, bisexual, transgender, and queer [LGBTQ+]). These findings highlight the need for continued primary prevention efforts. Additional screening to recognize adolescent SVP can allow both early treatment of depression and PTSD and address the individual risks of SVP to reduce subsequent repeated sexual assaults.